The evaluation of oxidative stress parameters in breast and colon cancer - Kundaktepe, Berrin Papila; Sozer, Volkan; Durmus, Sinem; Kocael, Pinar Cigdem; Kundaktepe, Fatih Orkun; Papila, Cigdem; Gelisgen, Remise; Uzun, Hafize (LIPPINCOTT WILLIAMS & WILKINS, 2021)
Our aim in this study was to investigate the relationship between serum ischemia modified albumin (IMA) levels with oxidative stress parameters [protein carbonyl (PCO), advanced protein oxidation products (AOPPs), malondialdehyde (MDA), total nitric oxide (NOx), prooxidant-antioxidant balance (PAB), and ferric reducing of antioxidant power (FRAP)] in breast cancer (BC) and colon cancer (CC). In total, 90 patients undergoing surgical treatment for BC (n = 45) or CC (n = 45) and 35 healthy controls were included in this cross-sectional study. The serum PCO, AOPPs, MDA, NOx, PAB, and IMA levels were all statistically significantly higher in the cancer patients than in the control group. MDA, NOx, and PAB levels were significantly lower in the BC group than in the CC group. FRAP values were statistically significantly lower in both the CC group and the BC group compared to the control. IMA showed a weak positive correlation with CA-19.9 (r = 0.423 P = .007) but a moderate positive correlation with tumor size in the CC group. IMA showed a positive correlation with metastasis, grade, and HER2 and a negative correlation with ER and PR in the BC group. Oxidative stress is a key player in the development of solid malignancies. Cancer development is a multistage process, and oxidative stress caused by the production of ROS/RNS in the breast and colon may predispose individuals to BC and CC. Patients with BC and CC had an impaired oxidative/antioxidant condition that favored oxidative stress. The ROC analysis indicated that IMA sensitivity above 80% could be used as a secondary biomarker in diagnosis.
Keywords: advanced protein oxidation products; breast cancer; colon cancer; ischemia modified albumin; malondialdehyde; nitric oxide; prooxidant-antioxidant balance; total antioxidant capacity; ISCHEMIA-MODIFIED ALBUMIN; PROTEIN PRODUCTS; MARKER; THIOREDOXIN; CARBONYL; RISK; General & Internal Medicine